2017
DOI: 10.1007/s12010-017-2445-0
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Recombinant Glucose Isomerase for Efficient Production of High Fructose Corn Syrup

Abstract: Glucose isomerase is the important enzyme for the production of high fructose corn syrup (HFCS). One-step production of HFCS containing more than 55% fructose (HFCS-55) is receiving much attention for its industrial applications. In this work, the Escherichia coli harboring glucose isomerase mutant TEGI-W139F/V186T was immobilized for efficient production of HFCS-55. The immobilization conditions were optimized, and the maximum enzyme activity recovery of 92% was obtained. The immobilized glucose isomerase sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 15 publications
3
13
1
Order By: Relevance
“…In these reports, most GIs did not achieve a conversion of 55%, some enzymes achieved a conversion of 55% at low-glucose concentrations, and there was no description of the relationship between conversion and substrate concentration. The results of this study showed that the conversion rate of CbGI increased with the increase of substrate concentration, which is somewhat different from previous reports, such as the conversion rate of GI from Thermus oshimai increased first and then decreased [22]. This indicates that CbGI has strong substrate tolerance.…”
Section: Conversion Efficiency Of Cbgicontrasting
confidence: 99%
“…In these reports, most GIs did not achieve a conversion of 55%, some enzymes achieved a conversion of 55% at low-glucose concentrations, and there was no description of the relationship between conversion and substrate concentration. The results of this study showed that the conversion rate of CbGI increased with the increase of substrate concentration, which is somewhat different from previous reports, such as the conversion rate of GI from Thermus oshimai increased first and then decreased [22]. This indicates that CbGI has strong substrate tolerance.…”
Section: Conversion Efficiency Of Cbgicontrasting
confidence: 99%
“…This result unveiled an increment shelf life thanks to the immobilization of GICA. Similar trend was also observed in previous study (Jin, et al, 2017).…”
Section: Storage Stabilitysupporting
confidence: 92%
“…Similar results about improving thermostability of immobilized GIs using various supports have been reported in literature (Araya, Urrutia, Romero, Illanes, & Wilson, 2019;Jia, et al, 2018;Jin, et al, 2017;Tükel & Alagöz, 2008). As example, Chen et al, described that the residual activities for free and immobilized GI from Streptomyces rubiginosus onto Eupergit C 250L were 97 and 84%, respectively after 18 h incubation at 60 °C (Tükel & Alagöz, 2008).…”
Section: Influence Of Temperature On Enzyme Activity and Stabilitysupporting
confidence: 78%
See 2 more Smart Citations